CULIARITIES OF KNOWLEDGE OF NATURE IN THE EARLY STAGES OF SOCIAL DEVELOPMENT - Sidorkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The interaction of nature and society includes issues related to modern man’s understanding of the scientific foundations of rational environmental management and the inclusion of environmental issues in the structure of the individual’s value imperative. The aim and tasks are to analyze the cultural and ecological dimensions of individual and collective existence at the early stages of social development. Research methods. include the dialectical approach in understanding the interaction of nature and society, as well as the results of philosophical studies of the communicative aspects of cognition and the spiritual and practical interaction of the cognizing subject with the objective world. Research results. At the heart of the relationship of traditional societies with the environment in their specific practical-activity aspect was the non-difference of being in the form of non-differentiation and poor technical equipment of labor, which gave rise to the non-difference of social and individual consciousness. Significant dependence of an individual of a traditional society on nature led to the formation of various geographically determined ethno-ecological systems, within which the basic principles of ecological culture were formed. Discussion. Ethno-ecological systems are cultural and historical types formed in various environmental conditions. The ecological culture of traditional societies performed the functions of a means of self-organization and regulation of the balance in the "man-biosphere" system, having the potential for cultural adaptation of human groups to changing environmental conditions in the context of the sustainable development strategy. Conclusion. The cultural and ecological foundations of human being in traditional societies in their specific practical and activity dimensions were determined by several basic principles: the non-diffusion of social being and the associated non-diffusion of social and individual consciousness, its religious and mythological nature. An important component of the substrate-procedural basis for the development of the environment was ecological culture, which, in the conditions of traditional society, performed regulatory functions in ensuring rational nature management and maintaining stability in the "man-biosphere" system.